PENGEMBANGAN PELAYANAN PUBLIK MELALUI E-GOVERNMENT (Studi Pada Layanan Smartcity Kabupaten Situbondo) - Syahrul Ibad; Yona Wahyu Lolita (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
The development and study of e-government carried out by the Situbondo Regency through the Communication and Information Office of the Situbondo Regency through the material plan, preparedness of concepts, targets, strategies, roadmaps, and application integration, besides the need to unify understanding of e-government so that there is no understanding anymore which tends to vary. Another problem that also arises is the readiness of supporting infrastructure, control and maintenance of the running of e-government also needs to be planned and made a clear legal umbrella. If so it is necessary to know the implementation of the development of public services through e-government carried out by the Situbondo Regency government both covering the success of the development of the system and its implementation. This research focuses on the stages of e-government development in order to achieve good governance which contains 4 stages (1) presence; (2) search, download (3) transaction and (4) transformation. Found in the development of services through e-government through; provision of facilities for public access (infrastructure), formulation of policies, determining the vision and mission, preparation of priority scale or master plan, education and training of human resources, the existence of public service contracts through e-government, and socialization to the implementing bureaucracy and the community. Done through a shared understanding of e-government between SKPD and the community, so that the stages of development and implementation can provide solutions to the challenges and problems of e-government.